The Dynamic of Challenges of Managing Functional Civil Servant in Malang Regency Indonesia - Mohammad Nuh; Suhartono Winoto; M. Rizki Pratama (Journal of Governance, 2022)
: Simplifying the bureaucracy is a vocal policy priority initiated by President Joko Widodo. Basically, the simplification of the bureaucracy tries to rebuild the bureaucracy based on functions and expertise which ultimately results in better output and performance. So far, the consequence is the transfer of structural positions to functional positions. These changes also have an effect on changes in the management of the state civil apparatus (ASN). Even though the management of functional positions in regional government is still a formidable challenge. Therefore, this research aims to describe the various problems of managing functional positions in local government, which are increasingly complex with the presence of the obligation to simplify the bureaucracy. Researchers conducted interviews with multiple parties, both with managers of functional positions and with individuals who have functional positions in the Malang Regency Government. The results of this study show the dynamics of the problem from three aspects, namely, first from a comparative point of view in the era of bureaucratic simplification, which shows the lack of clarity in policies seen from policy clarity, policy direction, and policy effectiveness. The second point of view of the actor is that of a functional official who experiences various human resource management problems as a functional official. The third point of view is the management of functional positions that face cultural and structural challenges such as habits and human resources management at the local level.